Implantable Subacromial Balloon Spacers in Patients With Massive Irreparable Rotator Cuff Tears: A Systematic Review of Clinical, Biomechanical, and Financial Implications - William L. Johns, B.S; Nikhil Ailaney, B.S; Kevin Lacy, B.S; Gregory J. Golladay, M.D; Jennifer Vanderbeck, M.D; Niraj V. Kalore, M.D (Elsevier, 2020)
Purpose: To determine the clinical, biomechanical, and financial impact of the use of subacromial balloon spacers in the surgical management of massive, irreparable rotator cuff tears (RCTs). Methods: All studies assessing the use of implantable subacromial balloon spacers for management of massive, irreparable RCTs were systematically searched. Risk of bias was assessed using Methodological Index for Non-Randomized Studies criteria. Data extraction and analysis was performed for pain and function scores, shoulder range of motion (ROM), glenohumeral contact pressure and vertical migration of humeral head, and cost. Subjective synthesis was performed with forest plots when outcomes were reported in 3 or more studies. Results: In total, 19 studies met inclusion criteria for analysis; 337 patients (mean age 68 years) had 343 subacromial balloon spacer implantations. Throughout a mean follow-up of 33 months, there was significant improvement in the Total Constant Score (preoperative: 22.5-41.8; postoperative: 51.4-72.3), Oxford Shoulder Score (preoperative: 21.3-26; postoperative: 34.39-48.2), American Shoulder and Elbow Surgeons score (preoperative: 24.5-59.1; postoperative: 72.5-85.7), and shoulder ROM parameters. Subacromial balloon spacer placement resisted superior humeral head migration (range of preoperative to postoperative difference: 2.8-6.2 mm) and decreased peak subacromial pressure during shoulder ROM. Conclusions: Existing literature of subacromial balloon spacers has a high risk of bias, lack of appropriate control, and low levels of evidence. A qualitative synthesis indicates that subacromial balloon spacer implantation in patients with massive irreparable RCTs is cost-effective and leads to improved function (Total Constant Score and Oxford Shoulder Score) and ROM. In cadaveric studies, subacromial balloon spacers resist superior humeral head migration and reduce subacromial pressure. The theoretical risk of biodegradation of the balloon spacer has not been substantiated in study of up to 5-years follow-up, and the risk of complications from this procedure appears to be minimal. Level of Evidence: IV; Systematic review of level III-IV studies.